Cariology consensus for undergraduates at dental schools in the Caribbean region. (7th January 2021) - Abreu‐Placeres, Ninoska; Grau‐Grullón, Patricia; Naidu, Rahul; García‐Godoy, Franklin; Newton, Jonathon Timothy; Ekstrand, Kim R.; Pitts, Nigel; Lopez del Valle, Lydia M.; Féliz‐Matos, Leandro; Rivera, Yilda; González, Ramón F.; Rajendra Santosh, Arvind Babu; et al.
Abstract: Aim: To obtain a consensus on the domains of cariology for undergraduates in dental schools in the Caribbean. Materials and Methods: Dental school deans from the Dominican Republic (DR) and Puerto Rico (PR) were invited to participate. Afterwards, 24 cariology faculty members from the dental schools in the DR received a 40‐h workshop on the current understanding of dental caries. Then, representatives from participating dental schools in the DR and PR were divided into six groups and tasked with exploring the cariology domains described in the European and Colombian consensus. For each domain, the competencies in what the dental student, upon graduation, would have to (1) be proficient in, (2) have knowledge of, (3) and be familiar with were described. Two cariology consensus meetings to work on the domains and suggest changes for the Caribbean region were done, and representatives from the DR and PR agreed on a cariology consensus. For the second stage, Caribbean English‐speaking countries were invited to participate in the consensus. Meetings were held with representatives from dental schools in Trinidad and Tobago (TT) and Jamaica (J) to include their suggestions on each consensus domain. Results: A total of 15 dental schools (DR = 12; PR = 1; TT = 1; and J = 1) participated; they agreed on a new consensus considering the realities of the Caribbean participating countries. Conclusion: A cariology consensus for undergraduates was achieved for 15 dental schools in the Caribbean region. This accomplishment will promote a shift for the Caribbean dental schools' graduates towards a current understanding of dental caries.